Sustained Ultrastructural Changes in Rat Hippocampal Formation After Repeated Electroconvulsive Seizures - Chen, Fenghua (Int J Neuropsychopharmacol, 2020)
BACKGROUND: Electroconvulsive therapy (ECT) is a highly effective and fast-acting treatment for depression used in the clinic. Its mechanism of therapeutic action remains uncertain. Previous studies have focused on documenting neuroplasticity in the early phase following electroconvulsive seizures (ECS), an animal model of ECT. Here, we investigate whether changes in synaptic plasticity and nonneuronal plasticity (vascular and mitochondria) are sustained 3 months after repeated ECS trials. METHODS: ECS or sham treatment was given daily for 1 day or 10 days to a genetic animal model of depression: the Flinders Sensitive and Resistant Line rats. Stereological principles were employed to quantify numbers of synapses and mitochondria as well as length of microvessels in the hippocampus 24 hours after a single ECS. Three months after 10 ECS treatments (1 per day for 10 days) and sham-treatment, brain-derived neurotrophic factor and vascular endothelial growth factor protein levels were quantified with immunohistochemistry. RESULTS: A single ECS treatment significantly increased the volume of hippocampal CA1-stratum radiatum, the total length of microvessels, mitochondria number, and synapse number. Observed changes were sustained as shown in the multiple ECS treatment group analyzed 3 months after the last of 10 ECS treatments. CONCLUSION: A single ECS caused rapid effects of synaptic plasticity and nonneuronal plasticity, while repeated ECS induced long-lasting changes in the efficacy of synaptic plasticity and nonneuronal plasticity at least up to 3 months after ECS.